THE EFFECT OF RESPONSIVENESS, EFFICIENCY, RELIABILITY, SECURITY ON CUSTOMER SATISFACTION AND LOYALTY USING THE LIVIN BY MANDIRI APPLICATION ON BANK MANDIRI KCP DEPOK 1 CUSTOMERS - Trisnawati, Sinta; Wijaya, Erric (Ibs Press, 2024)
This study aims to test and analyze the effect of Responsiveness, Efficiency, Reliability, Security, on Customer Satisfaction and Loyalty Using the Livin by Mandiri Application on Bank Mandiri KCP Depok 1 Customers. Primary data collection was carried out for 1 month using a research sample of 99 respondents. This study used a descriptive research design approach with empirical data collected through online surveys. Empirical data is then processed using the Structural Equation Modeling approach to test a number of hypotheses proposed. The results of this study Responsiveness affect Customer Satisfaction and Customer Satisfaction affects Loyalty. Meanwhile, Efficiency, Reliability, Security does not affect Customer Satisfaction.